MOGAD AS AN EMERGING CHALLENGE IN MODERN HEALTHCARE: FROM IMMUNOLOGY TO FUNCTIONAL RECOVERY - Żurek, Katarzyna; Rędziniak, Patrycja; Rajs, Monika; Przebieradło, Patrycja; Żak, Sandra; Ruzik, Alicja; Gaj-Hunter, Antonina; Kowalska, Monika; Stolarska, Kaja; Terpiłowska, Sandra; Żurek, Małgorzata; Wojciechowski, Piotr (International Journal of Innovative Technologies in Social Science, 2026)
Background. Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is a recently defined autoimmune demyelinating disorder of the central nervous system, characterized by antibodies against myelin oligodendrocyte glycoprotein (MOG).Aim. The aim of this review is to systematize the most recent evidence regarding the MOGADMaterial and Methods. A systematic literature review was conducted through a comprehensive search of databases (via the PubMed and Google Scholar platforms)Results. MOGAD may occur at any age, most frequently between 20 and 40 years, with variable epidemiological patterns. The clinical spectrum includes optic neuritis, transverse myelitis, acute disseminated encephalomyelitis (ADEM), cortical encephalitis, and brainstem or cerebellar involvement. Age-related phenotypic differences are observed, with ADEM predominating in children and optic neuritis being more common in adults. Biomarkers such as serum MOG-IgG titers, cerebrospinal fluid (CSF) leukocytosis, and oligoclonal band status may reflect disease activity and help predict relapse risk. Persistent seropositivity is associated with a higher likelihood of recurrence, whereas transient positivity correlates with a more favorable course. Acute management primarily includes high-dose corticosteroids, intravenous immunoglobulins (IVIG), and plasma exchange (PLEX). Long-term treatment involves immunomodulatory or immunosuppressive therapies, with oral corticosteroids and IVIG demonstrating the best balance of efficacy and tolerability.Conclusions. MOGAD represents a distinct immunological entity with specific clinical, radiological, and serological features. Ongoing research continues to refine diagnostic criteria, biomarkers, and therapeutic strategies, improving disease recognition and management.